Attitudes and behavior of drinking adults until 40 year of life towards beer - Suszek-Namroży, A.; Mironiuk, K. (Scientific Journal of Gdynia Maritime University, 2017)
Beer is one of the most popular alcohol beverage among Poles. It is being consumed at least a couple times a year, by almost 73% of adults, which gives about 23 million consumers. The aim of the study was to cognize attitudes and behavior of people between 18–40 year of life towards beer. Drinking occasionally was manifested by 38,74% of respondents, and the most popular place of consumption turned out to be bars and pubs (35,14%). Almost 40% of analyzed group was choosing places that offered a variety of imported beers and locally brewed ales. Desire to look for and to try craft beers was suggested by 62% of respondents.